recur - % i.e., x0 = [x[n0-M],. ..,x[n0-1]] % the output,...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
function y = recur(a,b,n,x,x0,y0); % % y = recur(a,b,n,x,x0,y0) % solves for y[n] from: % y[n] + a1*y[n-1] + a2*y[n-2]. .. + an*y[n-N] % = b0*x[n] + b1*x[n-1] + . .. + bm*x[n-M] % % a, b, n, x, x0 and y0 are vectors % a = [a1 a2 . .. aN] % b = [b0 b1 . .. bM] % n contains the time values for which the solution will be computed % y0 contains the initial conditions for y, in order, % i.e., y0 = [y[n0-N], y[n0-N+1], . ..,y[n0-1]] % where n0 represents the first element of n % x0 contains the initial conditions on x, in order
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: % i.e., x0 = [x[n0-M],. ..,x[n0-1]] % the output, y, has length(n) % N = length(a); M = length(b)-1; if length(y0) ~= N, error('Lengths of a and y0 must match') end if length(x0) ~= M, error('Length of x0 must match length of b-1') end y = [y0 zeros(1,length(n))]; x = [x0 x]; a1 = a(length(a):-1:1); % reverses the elements in a b1 = b(length(b):-1:1); for i=N+1:N+length(n), y(i) = -a1*y(i-N:i-1)' + b1*x(i-N:i-N+M)'; end y = y(N+1:N+length(n));...
View Full Document

Ask a homework question - tutors are online